Exploration of Role of Economic Globalization on Human Longevity - Ijaz, Bakhtawar; Arshed, Noman; Abbas, Zamin; Hanif, Uzma; Hameed, Kamran (iRASD Journal of Economics, 2021)
Recent developments which were coined to the opening up of borders have attracted interest of many researchers from many disciplines. A lot of work can be observed regarding the role of globalization / internationalization on economic growth and social development, this study specifically explores the implications of globalization on the ultimate goal that is life longevity. Adapting from the Kuznets curve, this study proposed a quadratic function of economic globalization and life longevity. The results using panel the ARDL model for the SAARC region, it can be seen that expansion of trade globalization de jure and management of financial globalization de facto and de jure may help them to increase longevity in the long run.